Myopic Strain: a normalized metric concept for assessing axial myopia - Ren, Qi; Chu, Zhe (Frontiers in Ophthalmology, 2025)
Axial myopia is characterized by excessive axial elongation, traditionally quantified by axial length (AL). However, AL conflates the eye’s focal distance (adaptive to refractive power) with defocus distance (excessive axial elongation). In this study, we developed Myopic Strain, defined as the ratio of retinal defocus distance (ΔAL) to the eye’s focal length, yielding a normalized metric for assessing axial myopia. In an analysis of 242 eyes, ΔAL and Myopic Strain were derived from Morgan’s optometric model. Subsequently, the correlation between Myopic Strain and optical and biomechanical markers of myopia was analyzed. Finally, we analyzed the distinctive characteristics exhibited by Myopic Strain and the ratio of AL to corneal curvature radius (AL/CR) as AL increased. Results demonstrated that Myopic Strain showed significant correlations with optical and biomechanical markers of myopia—spherical equivalent refractive error (SER; r = –0.81) and stress-strain index (SSI; r = –0.30) (both p < 0.001). Correspondingly, Myopic Strain provided superior explanatory power for SER (R² = 0.65) and comparable power for SSI (R² = 0.09) (both p < 0.001). Furthermore, our analysis revealed a strong positive correlation between Myopic Strain and AL (r = 0.82, p < 0.001), concomitantly with a moderate positive correlation between AL/CR and AL (r = 0.64, p < 0.001). Notably, the theoretical emmetropization baseline of AL/CR exhibited an inverse relationship with AL. In conclusion, Myopic Strain emerges as a suitable normalized metric for assessing axial myopia severity.